The Immune Microenvironment in Prostate Cancer: A Comprehensive Review - Novysedlak, Rene; Guney, Miray; Al Khouri, Majd; Bartolini, Robin; Koumbas Foley, Lily; Benesova, Iva; Ozaniak, Andrej; Novak, Vojtech; Vesely, Stepan; Pacas, Pavel; Buchler, Tomas; Ozaniak Strizova, Zuzana (Oncology, 2025)
BACKGROUND: Prostate cancer (PCa) is a malignancy with significant immunosuppressive properties and limited immune activation. This immunosuppression is linked to reduced cytotoxic T cell activity, impaired antigen presentation, and elevated levels of immunosuppressive cytokines and immune checkpoint molecules. Studies demonstrate that cytotoxic CD8+ T cell infiltration correlates with improved survival, while increased regulatory T cells (Tregs) and tumor-associated macrophages (TAMs) are associated with worse outcomes and therapeutic resistance. Th1 cells are beneficial, whereas Th17 cells, producing interleukin-17 (IL-17), contribute to tumor progression. Tumor-associated neutrophils (TANs) and immune checkpoint molecules, such as PD-1/PD-L1 and T cell immunoglobulin-3 (TIM-3) are also linked to advanced stages of PCa. Chemotherapy holds promise in converting the "cold" tumor microenvironment (TME) to a "hot" one by depleting immunosuppressive cells and enhancing tumor immunogenicity. SUMMARY: This comprehensive review examines the immune microenvironment in PCa, focusing on the intricate interactions between immune and tumor cells in the TME. It highlights how TAMs, Tregs, cytotoxic T cells, and other immune cell types contribute to tumor progression or suppression and how PCa's low immunogenicity complicates immunotherapy. KEY MESSAGES: The infiltration of cytotoxic CD8+ T cells and Th1 cells correlates with better outcomes, while elevated T regs and TAMs promote tumor growth, metastasis, and resistance. TANs and natural killer (NK) cells exhibit dual roles, with higher NK cell levels linked to better prognoses. Immune checkpoint molecules like PD-1, PD-L1, and TIM-3 are associated with advanced disease. Chemotherapy can improve tumor immunogenicity by depleting T regs and myeloid-derived suppressor cells, offering therapeutic promise.
Keywords: Tumor-Associated Macrophages; nádorové mikroprostředí; Male; CD8; T cells; makrofágy spojené s nádory; regulační T-lymfocyty; Prostate tumor; Myeloid-derived suppressor cells; Prostatic Neoplasms; mužské pohlaví; Immunology; CD4; Immunotherapy; T-Lymphocytes, Regulatory; Tertiary lymphoid structures; lidé; Humans; nádory prostaty; Tumor-associated macrophages; imunoterapie; Neutrophils; Metastatic; Tumor Microenvironment